Korsets gåde – en undersøgelse af offerbegrebets filosofiske og teologiske implikationer - Knudsen, Annette Hjort (Dansk Teologisk Tidsskrift, 2021)
According to Asle Eikrem’s book “God as Sacrificial love”, the concept of the Christian God as a God of love is not coherent with the claim that Jesus was sacrificed on the cross for the redemption of human sins. Eikrem’s conclusion builds on a conceptual framework that describes the crucifixion as a self-sacrifice. His argument makes Jesus co-responsible, thus sanctioning the violent action. This way, evil becomes instrumental which is inconsistent with the notion of God as love. It is the intention of this article to show that (at least) one alternative conceptual framework makes it possible to maintain the view that the crucifixion was necessary for Jesus’ redemptive mission. The crucifixion is thus not inconsistent with, but rather a consequence of the conception of God as love. For Jesus to realize God’s incarnational intention of establishing a living fellowship with humanity is for him to realize a fellowship of experienced damnation followed by a truly redemptive resurrection.